(untitled) (Sinología hispánica. China Studies Review, 2021)
Spain is one of the main destination countries for contemporary Chinese immigrants. Since the beginning of the 21st century, the Chinese diaspora has been the largest Asian immigrant group in Spain. In addition to the continuous expansion of the volume of their ethnic group, the development of their associationism is also striking. As a result of the increase, both in the number and diversity of Chinese associations in Spain, it is becoming increasingly important to have a panoramic knowledge about the advancement of associations in this ethnic group and its characteristics, in order to better understand society civilian of the Chinese diaspora in Spain. The article applies the quantitative methods like Bigdata and Text mining, registering a total of 474 associations established by the Chinese diaspora in Spain and 377 elements of characteristics (EC) extracted from them. It shows that the associationism of the Chinese diaspora in Spain has developed through three stages and with increasingly accelerated rates. In the qualitative dimension, associationism shows progress towards an integral diversity, being the geographical and thematic characteristics of the associations the most representative of this diversity.